Free floating thrombus in the non atherosclerotic, non aneurysmal ascedent thoracic aorta – An rare entity /Case treated with anticoagulate therapy - Joković, Vuk M (Medicinski časopis, 2018)
Free floating thrombus (FFT) attached with healthy aortic wall in ascedent aorta is very rare condition discovered more frequently with introduction of new imaging modalities. One of the main causes of this condition is hypercoagulable conditions and the main manifestations are distal embolisations. Method:We report a case of 59 years old male who sufferd from acute ishemia of lower limb due to emboli from floating thrombus in ascedent throacic aorta. Embolus in lower limb arteries was detected by digital substractional angiography and FFT by computer tomography. Anticoagulation therapy was started immediatly. After surgical removal of embolus in lower leg, hypercoagulable disorder was revealed. On control computer tomography scan, conducted after 10 days, no sign of thrombus in ascedent aorta was seen. Disscusion:We believe that initial treatment strategy should be conservative anticoagulate therapy that in many cases would be also a optimal solution, however no studies confirmed this, neither medical treatment algorithm is suggested. Key words: free floating thrombus, ascedent aorta, anticogulant therapy.